Existence and Uniqueness of Solution to Nonlinear Boundary Value Problems with Sign-Changing Green’s Function - Zhang, Peiguo; Liu, Lishan; Wu, Yong Hong (Hindawi Publishing Corporation, 2013)
By using the cone theory and the Banach contraction mapping principle, the existence and uniqueness results are established for nonlinear higher-order differential equation boundary value problems with sign-changing Green’s function.The theorems obtained are very general and complement previous known results.